Historyczna analogia jako quasi oryginalizm. Uwagi na tle sprawy Bruen oraz „postbruenowskiego” orzecznictwa w zakresie konstytucyjności art. 18 U.S.C. 922(g)(3) - Maćkowska, Katarzyna (PRAWO i WIĘŹ, 2025)
This article raises the issue of the impact of Bruen -  a judgment which, within the framework of broadly understood originalism, creates a new method of interpretation based on historical analogy - on the example of how the constitutionality of 18 U.S.C. 922(g)(3) has been assessed in cases, in which Second Amendment restrictions extend to illegal users, i.e. United States v. Harrison, United States v. Conelly, and United States v. Daniels. The Bruen ruling itself is controversial, for instance due to the alleged challenges in applying this precedent by lower courts. The interpretation of the Constitution by the federal Supreme Court - an institution currently identified with the republican approach or even reduced to the role of a political emanation of Donald Trump's presidency - will remain the subject of not only a strictly legal, but also a political/attitudinal evaluation made by lower-level courts in casu. This may result in transformation of the common law system itself, as a precedent "using" the concept of originalism or living constitution will cease to be a binding guide in a process of law application, and instead becomes a substitute instrument for the legislative power tin order to enact a specific policy. Therefore, the abovementioned risks require ongoing analysis of how Bruen influences selected issues regarding the constitutionality of 18 U.S.C. 922